Drug Information Sources for Patients with Chronic Conditions in the Qassim Region, Saudi Arabia - Saeed Alfadly; Mohammed Anaam; Mohammed Alshammari; Saud Alsahali; Ejaz Ahmed; Abdulkareem Bin Mubarak; Abdullah Aldahouk; Muhanna Aljameeli (MDPI AG, 2023)
Appropriate drug information is vital for the correct use of drugs in pharmaceutical practice. Providing patients with educational advice on prescribed medication and on proper medication administration has become an essential part of the pharmaceutical care process. The objectives of this study were to identify patients' knowledge of prescribed medications, their desire for more information, and the sources of medication information in a population from Qassim, Saudi Arabia, using a cross-sectional descriptive study. Our target population consisted of adult patients with chronic illnesses receiving drugs at outpatient pharmacies. Nineteen pharmacies were selected based on convenience. After collecting their prescriptions, patients were asked to take part in the study by interviewers as they were leaving the pharmacies. The questionnaire used was pretested on 18 patients and then modified accordingly. questions investigated participants' knowledge of drug information, their wish for more information, and their sources of drug information, other than clinicians. Descriptive analysis was used to describe patients' physical details. The effect of sex, education, diagnosis, number of drugs, and age on knowledge of the purpose of drugs and the need for additional information were tested using Chi-square test. A total of 270 patients were interviewed, of whom 29.7% reported not knowing the purpose of at least one of their medications, and only reading a portion of the PILs. Of the patients sampled, 56.7% said they read the side effects section of the PIL, 43.3% reported reading the uses, while 27% read the contraindications. The drug -interactions section was the least read, with only 18.9% reporting reading it. A total of 57% of the patients reported that they needed more information about their medications. Highly educated patients reported using the PIL, social media, family and friends, TV, and newspapers as sources of drug information at significantly higher rates than patients with lower levels of education. Healthcare professionals should assess patient comprehension and the need for additional drug information, especially among patients with low levels of education. Additionally, healthcare professionals should consider other information sources used by their patients.